A Novel and Low-Complexity Algorithm of EDAS for Spatial Modulation Systems - Altin, Gokhan (IEEE communications letters, 2020)
One of the techniques that helps to reduce the error probability for communication systems is transmit antenna selection (TAS). TAS with maximizing the minimum Euclidean distance, called Euclidean Distance Antenna Selection (EDAS), achieves high transmit diversity for spatial modulation (SM) systems. This letter focuses on a novel, very simple and low complexity antenna selection algorithm for EDAS. The main idea of this work is based on using eigenvectors obtained from the eigendecomposition of the matrix composed from the transmit SM signal difference vector. However, due to the characteristics of the SM, only certain eigenvectors are sufficient to achieve the Euclidean distance instead of all possible combinations of transmitted symbols. In addition, an algorithm is given in this study to find the required eigenvectors without the need for eigendecomposition. Simulation results show that our proposed method exhibits same symbol error rate performance as conventional optimum EDAS, but having lower complexity.